Be alert to the possibility of medication overuse headache - Londero, Renata Gomes (Headache Medicine, 2023)
Affecting 1-2% of the world's population and representing up to 40% of patients in specialist headache services, medication overuse headache remains a challenge. Starting with the need to make professionals aware since basic care, through patient education and ending with adequate (and successful) management, there is still much to be done. This literature review seeks to draw attention not only to the importance of recognizing the condition, but mainly to bring out the latest in the best management of patients who suffer from pain more than 14 days a month and who still see analgesics as the only way to manage their pain.